Perhitungan Overall Equipment Effectiveness (Oee) Pada Line 5/4l45w PT. Otscon Safety Indonesia - Agung Sobirin; Kusnadi Kusnadi; Dene Herwanto (Jurnal Ilmiah Wahana Pendidikan, 2021)
The development of the manufacturing industry gives rise to global competition. The characteristics of the competition force the company to achieve world class performance through continuous improvement. The application of continuous improvement resulted in several methods, such as total preventive maintenance, total quality maintenance and just in time. One of the most frequently used method developments is total preventive maintenance (TPM). According to Mobley (2016) defines TPM as a comprehensive maintenance strategy based on a tool life cycle approach that can minimize equipment damage, production defects and work accidents. TPM involves everyone in the organization, from top level management to technicians. PT. Otscon Safety Indonesia is an auto parts supplier company. Currently PT Otscon Safety Indonesia produces automotive components for almost all leading automotive manufacturers such as Mitsubishi, Honda, Nissan, Suzuki and Astra Daihatsu Motor. To produce products that have good quality, PT Otscon Safety Indonesia always pays attention to the room, tools, materials and operators in it. The tools used by PT Otscon Safety Indonesia to produce their products use high-tech tools. To operate it requires an operator who must understand every step in the production process.